Witness protection unraveled - Black, Maggie K. (Black, Maggie K. Protected identities., 2020)
Living in witness protection won't stop Travis Stone from shielding two orphaned children whose grandmother was just attacked. But when his former partner, Detective Jessica Eddington, asks him to help bring down the group that sent him into hiding, agreeing could put them all at risk.